Reading material selection for bibliotherapy based on blood type in young adult groups - Susanti Agustina; Wan Satirah Wan Mohd Saman; Norshila Shaifuddin; Rafidah Abdul Aziz (Universitas Padjadjaran, 2022)
Blood type as biological information is still considered a prophecy and pseudoscience that still needs to be proven. It is the easiest and cheapest among other genetic identification tools.This study aimed to map reading material selections based on blood type personality. This study was a quantitative approach through cross-sectional survey. Identification was obtained from data in identity cards and laboratory blood type tests. The study population was 100 UPI LIS students with 80 samples of young adults aged 18-22 through random sampling with stratification. The samples were: 9 respondents with AB blood type and 25 with A blood type. Respondents of O and B blood types each followed the selection of the expected sample was 20 people. Each homogeneous sample filled out a questionnaire on reading material selection aspects. Results showed that 55.6% of the AB blood type chose non-fiction books such as 'how-to' related to hobbies, and 52% of A blood type tended to select non-fiction books that support their tasks and work. Also, 81.8% of B blood type chose fiction books and adventure stories opening up fantasy horizons, and 80% of O blood type chose books that did not always have to be brought to the big screen/filmed; however, they were recommended and told. In conclusion, this blood type personality model can identify young adult clients' profiles to develop bibliotherapy service programs in different types of libraries and make it easier for librarians and bibliotherapists to recommend reading materials suitable for the benefit of preventive-curative bibliotherapy.